2012
DOI: 10.1002/jor.22085
|View full text |Cite
|
Sign up to set email alerts
|

Eversion during external rotation of the human cadaver foot produces high ankle sprains

Abstract: While high ankle sprains are often clinically ascribed to excessive external foot rotation, no experimental study documents isolated anterior tibiofibular ligament (ATiFL) injury under this loading. We hypothesized that external rotation of a highly everted foot would generate ATiFL injury, in contrast to deltoid ligament injury from external rotation of a neutral foot. Twelve (six pairs) male cadaveric lower extremity limbs underwent external foot rotation until gross failure. All limbs were positioned in 208… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(87 citation statements)
references
References 32 publications
(47 reference statements)
2
84
1
Order By: Relevance
“…Healthy articular cartilage surfaces are smooth, and their interfaces have some of the lowest known coefficients of friction (on the order of 0.01) (Fung, 1993). Therefore it is expected that in situ bone kinematic and ligament responses under quasi-static loads should be smooth, and this has been demonstrated in PMHS tests Johnson & Markolf, 1983;Siegler et al, 1988;Wei et al, 2012). In this study, the refined model responses were substantially smoother, and therefore more physically realistic, than the baseline model responses.…”
Section: Gross Moment Talus Kinematic and Ligament Force Responsesmentioning
confidence: 59%
See 4 more Smart Citations
“…Healthy articular cartilage surfaces are smooth, and their interfaces have some of the lowest known coefficients of friction (on the order of 0.01) (Fung, 1993). Therefore it is expected that in situ bone kinematic and ligament responses under quasi-static loads should be smooth, and this has been demonstrated in PMHS tests Johnson & Markolf, 1983;Siegler et al, 1988;Wei et al, 2012). In this study, the refined model responses were substantially smoother, and therefore more physically realistic, than the baseline model responses.…”
Section: Gross Moment Talus Kinematic and Ligament Force Responsesmentioning
confidence: 59%
“…Stiehl et al (1992) used a more compliant fiberglass cast tape restraint and documented ATiF injury in combination with fibular fracture. Wei et al (2012) reported that dorsiflexion and eversion followed by axial loading and external rotation of the foot generated isolated ATiF injury in all six cadaver ankles tested. This led to the hypothesis that "eversion… predisposes the ATiF to injury, forming a basis for syndesmotic ankle sprains."…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations